The Design of Everyday Things, revised and expanded edition - and Norman, Donald A. (MIT Press, 2013)
Even the smartest among us can feel inept as we try to figure out the shower control in a hotel or attempt to navigate an unfamiliar television set or stove. When The Design of Everyday Things was published in 1988, cognitive scientist Don Norman provocatively proposed that the fault lies not in ourselves, but in design that ignores the needs and psychology of people. Fully revised to keep the timeless principles of psychology up to date with ever-changing new technologies, The Design of Everyday Things is a powerful appeal for good design, and a reminder of how – and why – some products satisfy while others only disappoint.